PEMODELAN REGRESI LINEAR BERGANDA UNTUK MENGANALISIS PENGARUH KONSUMSI RUMAH TANGGA, PEMBENTUKAN MODAL TETAP BRUTO, DAN PENGELUARAN PEMERINTAH TERHADAP PRODUK DOMESTIK BRUTO DI INDONESIA - Wiwik Tri Hardianti; Syifa Rahma Citta; Fajri Aditiya Dwi Kurniawan (Ikatan Dosen Menulis, 2026)
This study aims to analyze the effect of household consumption, gross fixed capital formation (GFCF), and government expenditure on Indonesia's Gross Domestic Product (GDP). The data used in this study are secondary data in the form of time series consisting of 51 observations. Prior to model estimation, stationarity tests were conducted to ensure the validity of the analysis for time series data. Subsequently, the analysis was carried out using a multiple linear regression model with the Ordinary Least Squares (OLS) approach. All data processing and statistical analyses were performed using EViews software. The results indicate that, simultaneously (F-test), household consumption, GFCF, and government expenditure have a significant effect on GDP, with an F-significance value of 0.0000206. However, partially (t-test), only household consumption has a positive and statistically significant effect on GDP, with a significance value of 0.000016. Meanwhile, GFCF and government expenditure do not show a statistically significant effect on GDP during the study period. The coefficient of determination (R²) of 0.4018 indicates that the model explains 40.18% of the variation in GDP. Based on the residual scatter plot analysis, the model is also free from heteroskedasticity problems. The findings of this study suggest that household consumption serves as the primary driving force of economic growth in Indonesia compared to investment and government expenditure variables.